Critical Evaluation of Poetry according to Qudameh Ben Jaafar - Omid Jahan Bakht Laili; Gholamreza Karimi Fard (دراسات فی اللغه العربیه و آدابها)
Â  Qudameh Ben Jaffar, the prominent critic of Abbasid period, caused a revolution in Arabic literary criticism as he was the first one who decided to create harmony and integration among poetry and thought. He tried to revolutionize subjective criticism and replace it with a criticism which was based on scientific principles and ideas including artistic criticism on the one hand and philosophical and logical criteria on the other hand. Qudameh tried to took into account the principles of literary criticism moreover, he respected critical and aesthetic terms that are nowadays frequently used in theoretical criticism. This paper aims to examine the critical viewpoints of Qudameh and identify the criteria that he established in the area of poetry criticism. His arguments centred on such elements of poetry as sentence, word, meter, rhyme and meaning. Thus, he specified an ranking order for the poetry as follows: 1. absolutely good, when all of the composing elements of poetry are at their peak of perfection, 2.absolutely bad, when all of the composing elements of poetry are weak, and 3.intermediate, neither good nor bad, when the bad and good properties of poetry are at the same level.